Wpływ stosowania wapna, popiołu z biomasy i kompostu oraz preparatu "Efektywne Mikroorganizmy" na plonowanie i komponenty plonu jęczmienia jarego = Effect of lime, biomass ash, compost and the Effective Microorganisms substance on the grain yield and yield components of spring barley - Jurgiel-Małecka, Grażyna; Gibczyńska, Marzena; Hury, Grzegorz; Lewandowska, Leokadia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The field experiment was conducted in 2013 in Duninowo. The factors under analysis were: I. 6 fertilization variants; II. 2 levels of microbiological preparation use. The aim of the research was the assessment of the effect of the use of ash from biomass, calcium fertilizers and bio-compost (BIOTOP) together with Effective Microorganisms microbiological substance on yield, its structure and physiological parameters of spring barley cultivar Sebastian.
Keywords: popioły z biomasy; biokompost; jęczmień jary; nawożenie; biomass ash; biocompost; spring barley; fertilization